Effect of Matrix Rhythm Therapy versus Interferential current therapy with Laser therapy on plantar heel pain: A randomized clinical trial - Bhatikar, Ketan Kirtikumar (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Heel pain is a highly prevalent problem in most developing and under-developing countries. There are many studies done that show beneficial effects by different manual and physical modalities and therapies yet there is more of research to be done on new modalities and therapies that are drug-free rapid in its effect. Objectives: The purpose of this study was to evaluate and compare the effect of matrix rhythm therapy with strengthening exercises v/s interferential current therapy (ICT) with laser therapy and strengthening exercise. Methods: 30 participants with the age group 30 to 50 years old, experienced heel pain at least of one-month duration were randomly assigned to receive matrix rhythm therapy v/s ICT and LASER therapy. Strengthening exercises for plantar fascia were the same for both the groups. Intervention for both the groups was given alternatively for 15 sessions at the center by a certified therapist. Visual Analogue Scale (VAS) for the early morning first step pain and stiffness and Planter Fasciitis Pain/Disability Scale and revised Foot Function Index (FFI). Results: The pain subscale scores of the FFI showed significantly better results for the patients managed with the matrix rhythm therapy. Analysis of the response rates to the outcome measures also revealed significant differences with respect to pain, activity limitations, and patient satisfaction, with greater improvement seen in the group managed with the matrix rhythm therapy strengthening exercise. Conclusion: In the present study both the therapies showed the beneficial effects. However, matrix rhythm therapy was more significant than IFT and Laser therapy.